Queen's Men Editions 2.0. - DJAIN, BENJAMIN (Renaissance & Reformation / Renaissance et Réforme)
The article focuses on the Queen's Men Editions (QME) project, which provides critical and performance editions of plays associated with the Queen's Men using the Linked Early Modern Drama Online (LEMDO) platform. Topics include the project's extensive annotations and multimedia integration, the adoption of Text Encoding Initiative (TEI) guidelines for transparency and consistency, and the user-friendly design of the LEMDO platform.